2021
DOI: 10.1111/jfd.13507
|View full text |Cite
|
Sign up to set email alerts
|

Immersion vaccines against Yersinia ruckeri infection in rainbow trout: Comparative effects of strain differences

Abstract: Yersiniosis is a globally distributed disease of mainly freshwater fish, causing a high level of mortality and significant economic losses in aquacultures (Ummey et al., 2021). The disease is also termed enteric redmouth disease (ERM) due to the specific clinical signs of subcutaneous haemorrhages in and around the mouth and throat in infected

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…A recent study reported the effect of ERM immersion vaccines against the pathogen Yersinia ruckeri in the rainbow trout, Oncorhynchus , mykiss based on both biotypes 1 and 2 with serotype O1 (Yang et al 2021 ). They showed that both vaccine biotypes 1 and 2 can protect the fish against the infection.…”
Section: Current Status Of Fish Vaccines and Its Applications-mentioning
confidence: 99%
“…A recent study reported the effect of ERM immersion vaccines against the pathogen Yersinia ruckeri in the rainbow trout, Oncorhynchus , mykiss based on both biotypes 1 and 2 with serotype O1 (Yang et al 2021 ). They showed that both vaccine biotypes 1 and 2 can protect the fish against the infection.…”
Section: Current Status Of Fish Vaccines and Its Applications-mentioning
confidence: 99%
“…The earliest response of IgM gene was recorded at 72 h after exposure to betanodavirus in European seabass [ 32 ]. Similarly, Yang et al [ 50 ] reported an increase in CD8-α gene expression in rainbow trout at 5 days post-challenge with Yersinia ruckeri . Although the detection of the expression of adaptive immune gene was unsuccessful in our study, evidence of an adaptive immune response was demonstrated with outstanding ELISA antibody titer detected from the challenged vaccinated fish.…”
Section: Discussionmentioning
confidence: 87%
“…Because both the infection dose and the exposure time were well within the ranges where Y. ruckeri can cause mortalities in O. mykiss [ 78 , 79 ], it is likely that the bacterial isolate ( Y. ruckeri O1 biotype 2 100415-1/4) was of low virulence. Indeed, other studies using the same isolate did not result in mortalities [ 80 ]. The only recorded mortalities occurred in the fish that had received the diet supplemented with the highest doses of β-glucan, although this difference was probably not meaningful.…”
Section: Discussionmentioning
confidence: 95%